Direct determination of kQ for Farmer-type ionization chambers in a clinical scanned carbon ion beam using water calorimetry - Osinga-Blättermann, Julia-Maria; Brons, Stephan; Jäkel, Oliver (Physics in medicine and biology, 2017)
Until now, the dosimetry of carbon ions with ionization chambers has not reached the same level of accuracy as that of high-energy photons. This is mainly caused by the approximately threefold larger uncertainty of the kQ factor of ionization chambers, which, due to the lack of experimental data, is still derived by calculations. Measurements of absorbed dose to water, Dw , by means of water calorimetry have now been performed in the entrance channel of a scanned 6 cm × 6 cm radiation field of 429 MeV/u carbon ions, allowing the direct calibration of ionization chambers and thus the experimental determination of kQ . Within this work, values for kQ have been determined for the Farmer-type ionization chambers FC65-G and TM30013. A detailed investigation of the radiation field enabled the accurate determination of correction factors needed for both calorimetric and ionometric measurements. Finally, a relative standard measurement uncertainty of 0.8% ( k = 1) could be achieved for the experimental kQ values. For both chambers, the experimental kQ factors were found to be about 1% larger than those tabulated in the German DIN 6801-1 protocol, whereas compared to the theoretical values stated in the TRS-398 protocol, the experimental kQ value agrees within 0.4% for the TM30013 chamber but is about 1% lower in the case of the FC65-G chamber.